Analisis Etika Penggunaan AI dalam Layanan E-Counseling: Perspektif Konselor Bersertifikat - Hana Rizqiani Khoirunnisa; Fadhilatin Nashihah (Yayasan Azhar Amanaa Yogyakarta, 2026)
The development of artificial intelligence (AI) in e-counseling services presents both opportunities and significant ethical challenges. Certified counselors are on the front lines in addressing the ethical dilemmas arising from the integration of AI technology into professional counseling practice. This Systematic Literature Review (SLR) aims to analyze and synthesize 25 internationally reputable journals (indexed in Scopus, Web of Science, and other reputable publishers) that discuss the ethical aspects of AI use in E-Counseling services from the perspective of certified counselors. The study identified six key ethical issues: (1) client privacy and data confidentiality, (2) informed consent in AI-client interactions, (3) algorithmic bias and fairness, (4) transparency and accountability of AI systems, (5) client autonomy versus dependence on AI, and (6) the professional competence of counselors in supervising AI. These findings are expected to serve as a scientific foundation for the development of AI ethics guidelines in counseling practice in Indonesia. The PRISMA-C ethical framework proposed in this study is expected to serve as a practical guide for certified counselors in Indonesia in responsibly adopting AI technology, as well as to provide input for the development of ABKIN’s digital code of ethics.